Edible bird nest (EBN) can inhibit influenza A virus by affecting autophagy pathway - Haghani, Amin; Safi, Seyedeh Nikoo; Omar, Abdul Rahman; Aminuddin, Nur Ain; Mehrbod, Parvaneh; Ideris, Aini (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Influenza A virus (IAV) is a causative agent of many worldwide epidemics with high mortality and morbidity that cause tremendous economy costs annually. This virus will invade the host cells through endocytic pathways and cause various changes in intracellular pathways. It has been seen that even a pathway like autophagy is involved in this virus life cycle to promote the virus assembly. This virus prompts the accumulation of autophagosomes by blocking the fusion of the lysosomes. Hence, this pathway can be a great target for antiviral agents. Hence, the aim of this study was to highlight inhibitory effects of Edible Bird Nest (EBN) extract against IAV infection and understand some of the molecular mechanism of action. Consequently, we have investigated the effects of four different enzyme treated EBNs against IAV and some autophagy markers. At first, the Influenza A virus (strain A/Puerto Rico/8/1934 H1N1) infected cells were treated with different concentration of these EBNs to determine the IC50 of these extracts. Afterwards, western blotting technique has been used to evaluate the autophagosome marker protein microtubule-associated protein light chain 3-II (LC3-II) in different treatments. In addition, the lysosomal activity has been determined by staining the cells with Lysotracker Red DND-99. The results demonstrated that EBN extracts in combined treatments with influenza A viruses significantly reduced the virus titer and increased the cell viability especially in post-penetration treatments (P<0.05) with IC50 range from 2.6 to 4.9 mg/ml depends on the preparation and type. Regarding the authophagy pathway, the amount of LC3-II has been significantly decreased after treatment of the infected cells with EBNs (P<0.05), which caused increasing of the lysosome activity. Accordingly, this study revealed that EBN can be an efficient antiviral agent and also showed the involvement of autophagy pathway in antiviral activity of EBN averse to influenza A virus.